Report on trend and progress of Banking in India 1999-2000 - Reserve Bank of India (Mumbai : Charan singh for the Reserve Bank of India, 2000)
This volume provides an overall view of the policy initiatives undertaken since 1999-2000, the financial performance of scheduled commercial banks during 1999-2000 and a perspective towards developing a more stable, efficient resilient and vibrant banking system.
Includes bibliographical footnotes
hza 31/01/2019
Loans
Keywords: Banking services; India